Regulation and proteolytic activity of ADAM12 metalloprotease - Solomon, Emilia A. (Kansas State University, 2009)
ADAMs (a disintegrin and metalloprotease) can influence multiple cellular processes involved in normal development and pathogenesis. ADAM12 expression levels are elevated in many pathological conditions including cancer, cardiovascular disease, and muscle regeneration. Recently, ADAM12 has emerged as a candidate cancer gene in a comprehensive genetic analysis of human breast cancers. The regulation of ADAM12 expression is poorly understood. Identification of new substrates for ADAM12 metalloprotease can expand our knowledge of processes in which ADAM12 is involved. Here, we show that ADAM12 expression is upregulated by transforming growth factor beta (TGF-beta), an essential signaling pathway for many cellular processes. This upregulation requires proteosomal degradation of a transcriptional repressor SnoN. Furthermore, breast cancer cell lines expressing high levels of SnoN have significantly impaired induction of ADAM12 by TGF-beta, suggesting an inverse correlation between SnoN and the extent of regulation of ADAM12 by TGF-beta. Additionally, we demonstrate that ADAM12 is one of the metalloproteases involved in shedding a Notch ligand, Delta like 1 (Dll1). The Notch signaling pathway plays a crucial role in cell fate decision during development and in adults. Cleavage of Dll1 by ADAMs occurs in cis and results in activation of Notch signaling in a cell-autonomous manner. Furthermore, the intracellular domain of Dll1 created after cleavage further enhances TGF-beta signaling in response to TGF-beta. Our analysis of breast cancer-associated mutations in the ADAM12 gene showed a lack of proper proteolytic processing of the ADAM12 protein and its mislocalization to the endoplasmic reticulum. Additionally, ADAM12 mutants show a dominant-negative effect on the processing of the wild-type ADAM12 and result in loss of the functional ADAM12 at the cell surface. Collectively, our results indicate a new mechanism of regulation of ADAM12 expression, expand the role of ADAM12 in the regulation of Notch signaling, and characterize cancer-associated mutations in the ADAM12 gene.
Keywords: ADAM12; TGF-beta; Notch; proteolytic processing; Biology, Cell (0379); Biology, Molecular (0307)